Revolutionary Unconventional Transmission Line Designs With Higher Line Loadability - Mushfiqul Abedin Khan; Mona Ghassemi (IEEE Access)
Traditionally, overhead AC transmission lines have been used to transfer electrical power from the generation to the distribution sector. The capacitance and inductance of these lines are significantly influenced by the size and arrangement of the subconductors in each phase, which in turn affects the transmission capacity. Conventional transmission lines typically employ a circular symmetry for the arrangement of subconductors in each phase. However, by altering the number and placement of these subconductors, the power transfer capacity of the lines can be significantly increased. Unconventional transmission lines leverage this principle by deviating from the traditional circular symmetry, resulting in a lower characteristic or surge impedance ( $Z_{c}$ ), which enhances the surge impedance loading (SIL). This paper introduces new designs for unconventional transmission lines, optimized under strict criteria to minimize corona discharge effects while maintaining a narrow corridor width (CW). Compared to a conventional transmission line from the literature—with a SIL of 996 MW and a line width of 24.6 meters (yielding a power density of 40.5 MW/m)—our optimally designed conventional HSIL line achieves a SIL of 1351 MW (a 36% increase) and a line width of only 8.4 meters (a 66% reduction), resulting in a power density of 160.8 MW/m (a 297% increase). Even greater improvements are observed with unconventional HSIL designs, reaching a SIL of 1592 MW—representing a 60% increase over the conventional line and an 18% improvement over the best conventional HSIL design. These findings offer promising prospects for the future of modern transmission networks.